Evaluación de parasitosis intestinal postratamiento farmacológico y educación sanitaria en escolares de Uchanchi, Guano-Chimborazo. - Vargas Barzallo, Carla Elizabeth (2024)
Intestinal parasites are one of the most common infections in humans. They are widely distributed throughout the world. The most affected population is children, mainly in lowand middle-income countries. This work fulfilled the objective of evaluating the prevalence of ectoparasites after the intervention in schoolchildren from Uchanchi, Guano, and Chimborazo. The research is applied, descriptive, correlational, field-based, and ambispective. It was necessary to perform a copro parasitological analysis of the students to demonstrate the change in prevalence in this population that was treated with antiparasitic treatment and hygiene-sanitary education. The research considered a sample of 65 students from the Unidad Educativa "Uchanchi." They agreed to participate spontaneously. It was vital to use Microsoft Excel and Stat View for data processing. The results show a decrease in parasite prevalence from 100 to 93.9% (X2=4.127; P=0.0422) after the intervention, with a significant reduction in Blastocystis sp. (96.9 to 78.5%) (X2=10.263; P=0.0014), Entamoeba hartmanni (40.2 to 18.5%) (X2=16.284; P<0.0001), Endolimax nana (72.3 to 49.2%) (X2=7.260; P=0.0071). The study shows that the intervention positively impacted Uchanchi's student population. Thus, it was possible to identify a significant decrease in parasite prevalence, although it is necessary to continue training in hygienic-sanitary measures to achieve parasite control in the population. The results of the surveys support the importance of continuing with educational programs that boost awareness among students to improve their health, incorporating anthropological strategies with ethnographic experience in indigenous and rural communities that contribute to the success of future interventions.